Nitrogen pollution control in the European Union: challenging the requirements of the Nitrates Directive with the Agenda 2000 proposals. (1st January 2001) - Brouwer, Floor; Hellegers, Petra; Hoogeveen, Marga; Luesink, Harry
Nitrogen pollution resulting from agricultural activities is a major threat to the quality of the European environment. This paper aims to qualify the importance of nutritional management in reducing nitrogen pollution from intensive livestock production and to quantify its potential results where applicable. Reform of agricultural policy may achieve the economic and environmental benefits of reducing nitrogen pollution in the European Union. The reform in 1992 of the arable crop regime of the Common Agricultural Policy (CAP), reducing cereal intervention price, significantly lowered the cost of reducing the protein content of compound feed. The consequent reduction in feed costs enabled the pig and poultry sectors to apply nutritional management measures to reduce nitrogen output without compromising profitability throughout the production chain. However, the world market price of soybean meal is shown to influence the effectiveness of a reduction in cereal prices due to CAP-reform. Hence small incentives, complementary with CAP reform, may be necessary to ensure that the shift towards environmentally friendly practices in feed formulation remains permanent. In order to minimise the negative effects on nitrogen pollution of low prices of soya and protein-based raw materials, environmental protection measures may be required to ensure low dietary protein levels in feed formulations.